2020
DOI: 10.1016/j.physbeh.2020.113027
|View full text |Cite
|
Sign up to set email alerts
|

The autonomic correlates of dysphoric rumination and post-rumination savoring

Abstract: Trait dysphoric rumination is a transdiagnostic factor associated with depression and anxiety that has also been linked with blunted respiratory sinus arrhythmia (RSA), an index of reduced emotion regulation capacity. However, the autonomic correlates of state dysphoric rumination remain unclear. We examined the physiological correlates of state dysphoric rumination and the potential repairing effects of savoring on autonomic functioning. To provide a comprehensive assessment of autonomic correlates, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Along these lines, both blunted and potentiated reactivity to laboratory challenges have been associated with maladaptive emotional reactivity and regulation (see Obradović & Boyce, for review). Similarly, we have found that both maladaptive (i.e., dysphoric rumination) and adaptive (i.e., positive savoring) emotion regulation strategies are associated with increases in sympathetic activation among healthy individuals (Stone et al., 2020). The association between crying and corresponding emotional changes also is dependent upon context, particularly in relation to interpersonal factors (Bylsma, et al., 2008).…”
Section: The Influence Of Context On Emotional Reactivity and Regulationmentioning
confidence: 75%
See 3 more Smart Citations
“…Along these lines, both blunted and potentiated reactivity to laboratory challenges have been associated with maladaptive emotional reactivity and regulation (see Obradović & Boyce, for review). Similarly, we have found that both maladaptive (i.e., dysphoric rumination) and adaptive (i.e., positive savoring) emotion regulation strategies are associated with increases in sympathetic activation among healthy individuals (Stone et al., 2020). The association between crying and corresponding emotional changes also is dependent upon context, particularly in relation to interpersonal factors (Bylsma, et al., 2008).…”
Section: The Influence Of Context On Emotional Reactivity and Regulationmentioning
confidence: 75%
“…Further, the lack of coherence among emotion response domains highlights the importance of examining within and cross‐level associations to gain a full picture of emotional functioning in MDD, as these complex interactions may also contribute to divergent findings. Although prior research has revealed only modest and inconsistent associations between physiology and self‐reported emotion and affective behavior (Mauss et al., 2005; Mauss & Robinson, 2009), complex interactions may still be uncovered, and associations may change with context (e.g., Stone et al., 2020).…”
Section: Characterization Of Within and Cross‐level Interactions Acromentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, clinicians and health researchers have investigated the role of savoring in treating autism ( Cai et al, 2018 ) and anxiety disorders ( Eisner et al, 2009 ); preventing depression ( Ford et al, 2016 ); reducing pain ( D’Raven et al, 2015 ); helping people cope with stress ( Samios et al, 2020 ), cancer ( Hou et al, 2017 ), and acquired physical disability ( Dunn and Brody, 2008 ); repairing the negative effects of state dysphoric rumination ( Stone et al, 2020 ); reducing the link between marijuana use and marijuana problems ( Luba et al, 2020 ) and reducing pain and opioid misuse risk ( Garland, 2021 ). Research with older adults has also investigated the role of savoring in promoting resilience ( Smith and Hollinger-Smith, 2015 ) and positive attitudes toward aging ( Bryant et al, 2021 ), improving physical health ( Geiger et al, 2017 ), buffering the deleterious effects of illness on subjective well-being ( Smith and Bryant, 2016 ), and lowering cardiovascular reactivity and boosting agency ( Borelli et al, 2020 ).…”
Section: Historical Evolution Of the Concept And Measurement Of Savoringmentioning
confidence: 99%